Comparative Study of the Level of Inflammatory Factors of Erythrocyte Sedimentation Rate and Reactive Protein C in Benign and Malignant Thyroid Nodules - Mohsen Eshraghi; Seyed Jalal Eshagh Hosseini; Fatemeh Sadat Razavinia; Enayatollah Noori (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the level of inflammatory factors of erythrocyte sedimentation rate and reactive protein C in benign and malignant thyroid nodules. Material and Methods: In this case-control study, patients who were referred because of an enlarged thyroid gland were selected, patients who had undergone surgery for the thyroid nodule were included in the study. Erythrocyte sedimentation rate and reactive protein C were measured before surgery in patients who were candidates for thyroid surgery. The histopathological records of patients were retrospectively reviewed. Relevant cases had a cytological evaluation of thyroid nodules by fine-needle aspiration cytology (FNAC). The mean of ESR / CRP in both groups was compared using an independent t-test (p>0.05). Results: In malignant tumor type, in all patients, with Pill (PTC), analyzes in the malignant group showed a significant difference between the mean ESR / CRP in both groups with and without thyroid history. Sub-analyzes in the malignant group were significantly different between the mean ESR / CRP in both groups with and without thyroid histories (p=0.009) (40.16 ± 28.81). The association between ESR and CRP, ESR / CRP and tumor size, ESR / CRP and age in each group as well as in the whole patients were evaluated using Pearson correlation test, which showed a positive association between ESR age and ESR (p=0.024, r=0.375). In the malignant group, a negative correlation was found between the age and the CRP rate (p=0.027, r=-0.441), and in the total patients between the age and the rate (ES=0.043, r=-0.256). Conclusion: Factors such as ESR and CRP, which are considered acute phase reactors and their levels increase in acute inflammatory conditions, may not have a significant increase in chronic inflammatory conditions and malignancies.